Solid Lipid-based Delivery System for Oral Delivery of Drugs: A Review - Patra, Dr. Ch. Niranjan (Asian Journal of Pharmaceutics (AJP), 2019)
Solid lipid-based drug delivery systems such as lipospheres, solid lipid nanoparticles, and nanostructured lipid carriers have high stability, high carrier capacity, feasibility of incorporation of both hydrophilic and hydrophobic substances, and feasibility of variable routes of administration, including oral, topical, and parenteral and pulmonary routes. Highly lipophilic and poorly water-soluble compounds that also undergo extensive presystemic intestinal metabolism are the ultimate candidates for incorporation into solid lipid-based drug delivery systems to obtain increased and less variable bioavailability (BA). Increase in biliary and pancreatic secretions, stimulation of lymphatic transport, improvement of intestinal wall permeability, reduction of metabolism and efflux activity, and alteration in mesenteric and liver blood flow, which appreciably contribute to improved oral BA of the drug.